P757 An evaluation of the provincial 'syphistory' campaign in british columbia, canada. (14th July 2019) - Ryan, Venessa; Cumming, Emma; Haag, Devon; Edward, Joshua; Otterstatter, Michael; Grennan, Troy; Schwandt, Jillian Arkles; Brownrigg, Bobbi; Gilbert, Mark; Wong, Jason
Abstract : Background: Infectious syphilis rates have been increasing in British Columbia (BC), Canada, primarily among gay, bisexual, and other men who have sex with men (gbMSM). In response, a provincial syphilis campaign ("Syphistory") was launched in January 2017, and included posters in venues frequented by gbMSM (physical and online) and a campaign-specific educational website. Goals of the campaign were to increase knowledge of syphilis and syphilis screening. Methods: Website metrics were collected and analyzed via Piwik Analytics tool. Pre and post-campaign surveys were conducted to assess knowledge of syphilis using a convenience sample of clients attending STI clinics in the Vancouver area. One-sided t-tests were used to analyze change in knowledge scores. Interrupted time series analysis was conducted to assess the change in syphilis screening rate among males before versus on or after January 2017. Results: During 2017 there were 4, 421 unique visitors to the Syphistory educational website, of which 71% were between February and April. Mean survey score pre-campaign was 8.96/12 (n=137) and 9.12/12 (n=266) post-campaign (p=0.223). Those who reported seeing the campaign demonstrated a greater knowledge of syphilis (mean 9.7/12 versus 8.9/12, p<0.001). Provincial syphilis testing volumes among males were 93, 311 and 101, 967 in the 12 months before and after campaign implementation, respectively. Adjusting for the historical trend of increasing syphilis screening, there was a statistically significant change in syphilis testing rate among males (p=0.03). Conclusion: Our campaign appeared to have reached people living in BC. Syphilis knowledge was high in our pre-campaign sample, which may represent a more educated cohort. Nevertheless, those who saw the campaign scored higher. Syphilis testing rate among males increased significantly after campaign implementation. Work is underway to evaluate the campaign among gbMSM. Disclosure: No significant relationships.